Influence of 37 Years of Nitrogen and Phosphorus Fertilization on Composition of Rhizosphere Arbuscular Mycorrhizal Fungi Communities in Black Soil of Northeast China - Wang, Qingfeng; Ma, Mingchao; Jiang, Xin; Guan, Dawei; Wei, Dan; Cao, Fengming; Kang, Yaowei; Chu, Changbin; Wu, Shuhang; Li, Jun (Frontiers in Microbiology, 2020)
Increased inorganic nitrogen (N) and phosphorus (P) additions expected in the future will endanger the biodiversity and stability of agricultural ecosystems. In this context, a long-term fertilizer experiment (37 years) was set up in the black soil of northeast China. We examined interaction impacts of elevated fertilizer and host selection processes on arbuscular mycorrhizal fungi (AMF) communities in wheat rhizosphere soil using the Illumina MiSeq platform. The soil samples were subjected to five fertilization regimes: no fertilizer (CK) and low N (N1), low N plus low P (N1P1), high N (N2) and high N plus high P (N2P2) fertilizer. Long-term fertilization resulted in a significant shift in rhizosphere soil nutrient concentrations. The N fertilization (N1 and N2) did not significantly change rhizosphere AMF species diversity, but N plus P fertilization (N1P1 and N2P2) decreased it compared with CK. Nonmetric multidimensional scaling showed that the rhizosphere AMF communities in CK, N1, N2, N1P1 and N2P2 treatments were distinct from each other. The AMF communities were predominantly composed of Glomeraceae, accounting for 30.0%–39.1% of the sequences, and the relative abundance of family Glomeraceae was more abundance in fertilized soils, while family Paraglomeraceae were increased in N1 and N2 compared with CK. Analysis shown that AMF diversity was directly affected by soil C:P ratio but indirectly affected by plant under long-term fertilization. Overall, the results indicated that long-term N and P fertilization regimes changed rhizosphere AMF diversity and community composition, and rhizosphere AMF diversity was both affected by soil C:P ratio and plant.